Whole-body cryotherapy (-110 °C) following high-intensity intermittent exercise does not alter hormonal, inflammatory or muscle damage biomarkers in trained males - Krueger, M.; Costello, J. T.; Achtzehn, S.; Dittmar, K. H.; Mester, J. (Cytokine, 2019)
This study examined the acute effects of a single session of Whole-body Cryotherapy (WBC) following severe intermittent running exercise on biomarkers of inflammation, muscle damage and stress. Methods: Endurance-trained males (n = 11) were tested twice using a within-participant, balanced cross-over design that consisted of 5 × 5 min of high-intensity running (HIR) followed by either 3 min of WBC at -110 °C or a passive control condition (CON). Before the HIR and after 60 min of recovery a ramp-test was completed. At seven time points up to 24 hrs post exercise venous blood samples were analyzed for serum levels of interleukin 6 (IL-6), interleukin 10 (IL-10), c-reactive protein (CRP), soluble intercellular adhesion molecule-1 (sICAM-1), myoglobin, cortisol, and testosterone. Results: HIR induced significant increases in all biomarkers except sICAM-1 in both recovery conditions, respectively. Compared to the CON condition WBC did not attenuate exercise- induced changes in IL-6, IL-10, sICAM-1, myoglobin, cortisol, testosterone or their ratio. Increased levels of cortisol following exercise were negatively correlated with subsequent running performance in both conditions (WBC: r = -0.61, p = 0.04; CON: r = -0.64, p = 0.04). Conclusion: The results of this study suggest that the postulated physiological mechanisms by which WBC is proposed to improve recovery, i.e. reductions in inflammation and muscle damage, may not be accurate.